Simbolisme dan Akulturasi Budaya dalam Arsitektur Istana Pagaruyung: Sebuah Pendekatan Semiotika - Ridwan Alwi; Dara Wisdianti (Jurnal Teknik dan Teknologi Indonesia, 2024)
This research aims to analyze the semiotic aspects in the architecture of Pagaruyung Palace, focusing on the symbolism, acculturation, and historical aesthetics contained in the building. Pagaruyung Palace, as one of the Minangkabau cultural heritages, not only serves as the residence of the king, but also as a place for the expression of cultural, social and political values of the Minangkabau people. Through a semiotic approach, this research examines the architectural elements of Pagaruyung Palace, such as the shape of the gonjong roof, the building structure, and the ornaments contained therein, which hold deep symbolic meanings. Furthermore, this research also explores the acculturation process that occurred in the architectural design, where the influence of various cultures, such as Malay, Hindu-Buddhist and Islamic, is reflected in the architectural elements. The aesthetic aspects arising from the fusion of these cultural elements are also analyzed to understand how the architecture of Pagaruyung Palace creates harmony between function and beauty. This research is expected to provide deeper insights into the relationship between architecture, culture, and history and its outcomes.